Productivity Drag from Small and Medium-Sized Enterprises in Japan - Colacelli, Mariana (IMF Working Papers; Working Paper ;, 2019)
Productivity growth in Japan, as in most advanced economies, has moderated. This paper finds supportive evidence for the important role of small and medium-sized enterprises (SMEs) in explaining Japan's modest productivity growth. Results show a substantial dispersion in firm-level productivity growth across sectors and even across firms within the same sector. SMEs, on average, exhibit lower productivity growth than non-SMEs in Japan, with smaller and older SMEs showing particularly low productivity growth. Estimates suggest that boosting productivity growth in all of the worst-performing SMEs could improve overall productivity growth by up to 1.8 percentage points. The SME credit guarantee system, SME financing constraints, demographic factors, and lack of intangible capital investment are discussed as contributors to the slow productivity growth of Japan's small and old SMEs.